LOUSADA, ISABEL. LORD GEORGE NUGENT GRENVILLE: BARON NUGENT OF CARLANSTOWN (1789-1850) E PORTUGAL. LISBOA: FONTE DA PALAVRA, 2016. 168 P. - Medeiros, Aldinida (Historiæ, 2017)
Recensão crítica: Portugal e as guerras sob a visão de um inglês: um poema épico de Lord Grenville.